Utrustning och utrymmen för uppbyggnad av en rehabiliteringsavdelning för hundar - Olsson, Moa (2012)
Physical rehabilitation is a constantly growing field in veterinary nursing. To build a physical rehabilitation center for dogs you need personnel with adequate education and knowledge. In spite of good knowledge it can be hard to know which areas and equipment necessary for the work. It is of interest to describe how a physical rehabilitation center can be planned and which spaces and equipment to prioritize. In this study, data of different spaces and equipment for a physical rehabilitation center for dogs are presented and also the economical perspective is introduced as a background. An internet based survey was e-mailed to 55 physical rehabilitation centers in Sweden (54) and Norway (1) of which 37 responded. The questions were about equipment and spaces in the rehabilitation center. Questions about the education of the personnel, about the most common patients and about the extent of veterinary cooperation were also in the survey. The result of the survey indicates which spaces and equipment are needed in a physical rehabilitation center and which ones are less important or useful.